The Impact of Front Office Service Quality on Customer Satisfaction: Evidence from Hospitality Sector in West Java - Ananta Budhi Danurdara; Nisrina Andranaswari Paramitha (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to explain and explore the links between service quality and customer satisfaction, emphasizing front-office service quality, and to explore the effect of the service quality of front-office staff at the Hospitality Sector in West Java on customer satisfaction. This study uses qualitative methods and relies on primary data derived from questionnaire responses. The number of respondents is 215 guests who are currently staying or have stayed at Hospitality Sector in West Java. The sampling technique was carried out by purposive sampling. The analysis was done descriptively, and it shows the analysis of service quality, guest expectation analysis, guest satisfaction analysis, gap analysis between two variables, and correlation analysis. The results of the study concluded that customer satisfaction with the services provided by the front office staff of Hospitality Sector in West Java as a whole has only reached 69.45%. Customers are most satisfied with the tangible dimension (X5), followed by the reliability dimension (X1), empathy dimension (X4), assurance dimension (X3), and responsiveness dimension (X2). Based on the correlation tests, it was found that the service quality (X) of the front office at Hospitality Sector in West Java has a positive effect on customer satisfaction (Y). To increase customer satisfaction, it is suggested to Hospitality Management in West Java to make service improvements, especially in the responsiveness dimension (X2). Furthermore, the management of Hotel in West Java can conduct the training program on delivering service and repair or replace the equipment that used in the front-office area to ensure comfort for guests.